The Renewal of an Ethnic Tradition and Its Role in Shaping the Kurds Immigrants' Identity. Issue 2 (4th May 2017) - Sharaby, Rachel
Abstract: The article discusses the Seharane celebrations of the Jews of Kurdistan whose immigration to Israel is a case of 'ethno-national homecoming'. The immigrants from Kurdistan express an Israeli identity in the public renewal of these celebrations. Their leaders demanded a right to ethnic otherness that is included in Israeli society, and attempted to position themselves anew within the national space. The syncretic dynamics that were created indicate that ethnic traditions continue to serve as a resource for minority groups of immigrants and their offspring, and that a liberal state must afford their customs public legitimisation and must recognise their leaders.